Pengembangan Media Pembelajaran Berbasis Web- Let's Learn Online Untuk Meningkatkan Kompetensi Siswa Pada Pembelajaran Pemasangan dan Konfigurasi Perangkat Jaringan Dengan Model PjBL - Putra, Dedy; Sujatmiko, Bambang; Dwikoranto, Dwikoranto; Lintangesukmanjaya, Rahmatta Thoriq; Bergsma, Lindsay N. (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective:  This study aims to produce WEB-Let's Learn Online to train the competency of installation and configuration of network devices of SMK students that are feasible (valid, practical, and effective). Method: This study is a type of development research employing the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included validation, questionnaires, observations, and tests, involving 66 students from an SMK in Surabaya. The validity of the module was assessed based on learning, material, language, and media aspects. Practicality was evaluated through implementation processes and challenges encountered in project-based student competencies. Effectiveness was measured by the improvement in student competencies. The assessment of validity, learning implementation, and project-based competencies was based on average scores. The web-based learning media was considered feasible if the percentage across all eligibility criteria. Results: The results of the study showed 1) The average validity score of the web-based learning media was categorized as very valid; 2) The average learning implementation score was indicating a very practical category. The average he post-test score was categorized as good; 3) The average N-gain value was the moderate category, and the t-test confirmed a significant increase in student competency, indicating the media is effective. Novelty: This website-based platform allows students to learn anytime and anywhere, effectively enhancing their competencies and digital literacy in installing and configuring network devices .